Prehistoria pamięci. Zagłada we wczesnym amerykańskim programie rozrywkowym - Pakier, Małgorzata (Zagłada Żydów. Studia i Materiały, 2011)
In the 1950s NBC regularly broadcast This Is Your Life! – a 30-minute talk show. The guests included well-known persons as well as unknown heroes of everyday life. A few times the invited guests were the so-called witnesses to history, including Holocaust survivor Czech Jewess Hanna Bloch Kohner. The episode of This Is Your Life! with Hanna Bloch Kohner is perhaps the first time that the Holocaust was used in a TV entertainment show after the war. The structural requirements of a new popular show genre forced the heroine to play a highly specific role, and the need to provide entertainment to the viewers significantly influenced the construction of her story. In that narration post-war American optimism clearly triumphed over the dramatic past of the European Jewish immigrant. This Is Your Life! broadcast Hanna’s story into a social context still insensitive to the historical dimension of the Holocaust. Hence, how does the not yet developed medium deal with such close and still unspecified history in the period of no fixed cultural references? To answer this question the author refers to the theory of collective memory and the notion of trauma on the one hand and to the theory of TV genres on the other.